5 Polnts
If f(x) = 2x² - 5 and g(x) = x2 - 4x - 8, find (f - g)(x).
O A. (8-9)(x) = -x2 - 13
O B. (8-9)(x) = x2 + 4x+ 3
O c. (- g)(x) = 3x² - 4x - 13
O D. (- g)(x) = x2 - 4x - 3​

Respuesta :

Answer:

B.  (8-9)(x) = x2 + 4x+ 3

Step-by-step explanation:  Hi there! So the question is what is (f-g)(x)?

So let's start off with what is f(x) and g(x)?

f(x) is 2x²-5 while g(x) is x²-4x-8

So how do we do this? We subtract the two!

2x²-5 - (x²-4x-8)  let's look at the g(x) function

-(x²-4x-8) (let's break it apart!

-(x²)= -x²    -(-4x) = +4x     -(-8)= +8  =>  -x²+4x+8  replace the original with the new for the problem

2x²-5-x²+4x+8   alrighty we have that the first thing to do is to combine like terms. Is there anything number or vairable that are the same? yes there is!

We see a 2x² and a negative x² => 2x²-x² would equal to x²

Next we see an -5 and a positive 8 =>  -5+8 equals to 3

Lastly, we have 4x. Where the other x variable? That's the thing? There is no. So in this case 4x is all alone.

With the answers we need to put them together. We would have...

x²+ 4x +3. That is the answer to (f-g)(x) in other words B.

Sorry about typing a lot. I love to explain in details lol. But if you have any questions or comments please don't be afraid to say anything! I really do hope I helped in any kind of way. Have a great day! :D